The Air Gap and Angle Optimization in the Axial Flux Permanent Magnet Motor - (:unkn) unknown (KAUNAS UNIV TECHNOLOGY, 2011)
C. Akuner, E. Huner. The Air Gap and Angle Optimization in the Axial Flux Permenant Magnet Motor // Electronics and Electrical Engineering. - Kaunas: Technologija, 2011. - No. 4(110). - P. 25-29. In this study, the axial flux permanent magnet motor and the length range of the air gap between rotors was analyzed and the appropriate length obtained. NdFeB permanent magnets were used in this study. Permanent magnets can change the characteristics of the motor's torque. However, the distance between permanent magnets and the air gap will remain constant for each magnet. The impact of different magnet angles for the axial flux permanent magnet motor and other motor parameters was examined. To this aim, the different angles and torque values of the magnetic flux density were calculated using the finite element method of analysis with the help of Maxwell 3D software. Maximum torque was obtained with magnet angles of 21 degrees, 26 degrees, 31.4 degrees, and 34.4 degrees. Additionally, an important parameter for the axial flux permanent magnet motor in terms of the air gap flux was analyzed. Minimum flux change was obtained with a magnet angle of 26 degrees. The magnetic flux of the magnet-to-air-gap is under 0.5 tesla. Given the height of the coil, the magnet-to-air-gap distance most suitable for the axial flux permanent magnet motor was 4 mm. Ill. 11, bibl. 4, tabl. 2 (in English; abstracts in English and Lithuanian).